A PIS Information Generation Method for Autonomous-rail Rapid TramBased on Module Reuse - XIONG Kai; HU Yunqing; WEN Biwang; HUANG Zhou; ZHANG Xin (Kongzhi Yu Xinxi Jishu)
In multi-line operation scenario, autonomous-rail rapid tram needs to operate in the same line and the same station, and traffic uncertainty is high under the condition of non-independent right of way on the road surface.Therefore, this paper proposed a PIS information generation method based on module reuse technology to solve the PIS information generation in multi-line operation mode. In this method, a modular object model is established by object-oriented thinking, and onboard signal data in multiple lines is processed by multi-channel real-time module multiplexing technology. According to the actual position and speed of the tram, scenes of pre-arrival, arrival and departure are simulated and calculated, and real-time accurate PIS information of the platform is generated. Simulation results verify the accuracy and stability of the method by importing the actual operation data of the autonomous-rail rapid transit in Yibin city.